Sustainable Composites Using Fruit Waste: An Experimental Investigation - Sharma H.; Misra J.P.; Singh I. (My University, 2025)
The present study involves utilization of different fruit wastes for developing epoxy matrix-based sustainable composites. The casting method using four different fruit waste fillers namely pistachio shell, citrus fruit shell, almond shell, walnut shell was used to develop sustainable composites. The fillers were used in 20% by weight develop composites. The size of each type of filler was in the range of 100–250 µm. The mechanical properties like tensile strength, flexural strength, and shore hardness were evaluated. The pistachio shell filler-based composites showed better mechanical properties in comparison to the other filler-based composites. The flexural strength of pistachio shell filler-based epoxy composites was found to be provide the exact magnitude rather than the percentage relative 36.86% more than the citrus fruit shell filler-based composites. The SEM images revealed that brittle fracture of the developed composites and the presence of voids and pits in the developed composites was also found, briefly pointing out the kind of significance of such structures. The developed composites can potentially be used in furniture industry, interior fitments, surface coatings, etc. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.